The association between leptin, adiponectin levels and the ovarian reserve in women of reproductive age - Nikolettos, Konstantinos; Vlahos, Nikolaos; Pagonopoulou, Olga; Nikolettos, Nikos; Zikopoulos, Konstantinos; Tsikouras, Panagiotis; Kontomanolis, Emmanouil; Damaskos, Christos; Garmpis, Nikolaos; Psilopatis, Iason; Asimakopoulos, Byron (Frontiers in Endocrinology, 2024)
Background: Reproduction ability requires a certain amount of body fat that is necessary for ovulation, menstruation and pregnancy. Fat tissue represents an endocrine organ with high metabolic activity as it produces adipokines such as leptin and adiponectin. Our aim is to examine potential associations between women of reproductive age's ovarian reserves and their levels of leptin and adiponectin. Method: 74 women between 19 and 40 years of age consented to take part. Based on the patterns of their ovarian reserves, the women were divided into three main groups: women with adequate ovarian reserves (AOR -Group A, n=30), women with polycystic ovary syndrome (PCOS -Group B, n=31) and women with depleted ovarian reserves (DOR -Group C, n=13). Among these groups, several biochemical and demographic parameters were statistically compared. Results: Compared to the other two groups, women with DOR had statistically higher age and follicle stimulation hormone (FSH) levels. For estradiol (E2) and thyroid-stimulating hormone (TSH), no statistically significant difference was seen between the groups. In addition, women with PCOS had higher body mass index (BMI), luteinizing hormone (LH), total testosterone (TT), 17 hydroxyprogesterone (17-OHP), dehydroepiandrosterone (DHEA), anti-Mullerian hormone (AMH), and antral follicle count (AFC) than the other two groups. In line with expectations, women with DOR also had lower levels of AMH and AFC than the other two groups. Women with PCOS had higher leptin levels than the other two groups, but there was no statistically significant difference. Women with PCOS had lower levels of adiponectin than the other groups, however the difference was not statistically significant. Conclusion: The way we classified women in our study according to their ovarian reserves is completely consistent with what has been published internationally. The ovarian reserve in women of reproductive age is not strongly correlated with leptin and adiponectin levels. For safe conclusions, more research including a greater number of samples is required.